Knowledge, attitudes and practices on dengue vectors of households in Tumagboc catchment area, Miagao, Iloilo. - Arbizo, Jeric L.; Baldevarona, Rosa Lea S.; Caoyonan, Louise Asuncion D.
Previous studies have shown that knowledge, attitudes and practices have an association with the dengue vector control. As such, the independence of mosquito population on the socio-demographic characterization and KAP of the household heads in Tumagboc Catchment Area, Miagao, Iloilo was tested. Based on the results, the heads generally are unemployed, married females aging 41 to 50. Their households are composed of 4 to 7 members with no or one child below 15 years, and usually receive below P 1999 per month. Most of them are informed about dengue fever, but only one had suffered from it in the last two years. Moreover, have moderate knowledge, poor attitudes, but good practices regarding dengue prevention. The container index is 2.71 for crude mosquito larvae and pupae population, and 0.39 for Aedes sp. The house index is 9.72, while the Breteaux indexis 13.19. Chi-square analysis at 0.05 level of significance confirmed the independence of mosquito larvae and pupae population from monthly income, dengue information reception, knowledge, attitudes and practices. A solid reason was the untimely conduct of the study in the beginning of the summer season, when stagnant water has dried up and with few vulnerable breeding sites.